Improving Resilience of Corn to Weather through Improved Fertilizer Efficiency - Na Huang; Gretchen F. Sassenrath; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2023)
Fertilization is a critical management tool to improve crop productivity. Corn requires more N fertilizer than some other crops, but the fertility needs of the crop vary based on the growing environment. In this study, we used a modeling approach to examine the historical record and delineate the interaction between fertilizer and weather on the sensitivity of corn yield to climate in southeastern Kansas. Providing optimal fertilizer can improve corn yield. However, too much fertilizer can be expensive and wasteful. This study demonstrated that the climate resilience of corn is moderated by how much fertilizer is applied. The model results concluded that the optimal N fertilizer rate should be adjusted based on weather conditions.
Keywords: corn; growing environment; fertilization efficiency; temperature sensitivity